Ihsan: The spiritual essence of Islam - Yaacob, Asiah; Abdulai, Kaba (Prince of Songkhla University, Pattani Campus, 2010)
Modern man is in search of spiritual solace to help relieve him of his mundane problems. In his search for such comfort he tends to land himself in the snare of some misguided spiritual claimants, who are packing religion to suit the person. Thus some are advancing the idea of segregation between the three fundamentals of Islam: iman, Islam and ihsan. This paper attempts to put the record straight by presenting the mutual inclusiveness of these terms with one another and how they complete the wholesomeness of the religion of Islam.